MONITORING BAYI BILIRUBIN PADA ALAT PHOTOTHERAPY MENGGUNAKAN MODUL KAMERA OV 7670 BERBASIS INTERNET OF THINGS - Hariyono, Muhammad Akbar; Syauqi, Muhammad Fuad; Rizkiansyah, Rakhmad; Saputra, M Risky (Politeknik Unggulan Kalimantan, 2023)
Cases of jaundice (hyperbilirubinemia) is a condition that is often found in newborns. About 50-70% of term babies and 80-90% of premature babies have hyperbilirubinemia. Jaundice or hyperbilirubinemia occurs due to too high levels of bilirubin in the blood. This situation occurs because the function of the liver (liver) in newborns is not yet perfect to break down and remove bilirubin from the body. When this happens, the skin and the whites of the baby's eyes are yellow (jaundice). At first, light therapy is done using natural methods, namely with a source of sunlight. However, due to the limited effective time for irradiation, which can only be done between 07.00-09.00 in the morning, this therapy cannot be carried out throughout the day. The development of this tool uses the Arduino uno control system and the OV 7670 camera module to make it easier for health workers to control babies. This tool has a speaker that has advantages for 2-way communication so that movement and sound will be heard on the user's cellphone. This research uses quantitative methods with a development research approach or better known as Research & Development (R&D). In the health sector, products produced through R&D research are expected to increase health productivity, namely security and safety when using tools. Based on the measurement results of the bluelight lamp, it was found that the wavelength value of the lamp got an average accuracy value of 96.26%. The results of the validation assessment from the material expert validator get an average interpretation value (81) and the media expert validator gets an average interpretation score (84), making the Bilirubin Baby Monitoring tool on the IoT-Based Photetherapy Tool 'Very Good' to use.